Manifestaciones folklóricas que hacen posible la práctica del turismo vivencial en el pueblo de cajabamba provincia del mismo nombre, región de cajamarca. - Calderón Campos, Yessica Geovanny (2015)
This paper tourism research called: folk events FOR THE PRACTICE OF LIVING TOURISM IN THE TOWN OF CAJABAMBA, PROVINCE OF THE SAME NAME, REGION OF TRUJILLO, aims to: Identify folk events presented by the people of Cajabamba province are the same name, Cajamarca region for the Practice of Experiential Tourism. Among the most outstanding folk events in the village of Cajabamba to practice Experiential tourism, this craft, characterized by the development of pottery, weaving colorful addition to paintings and pictures where the daily customs, landscapes and picturesque places is expressed Cajabamba; popular beliefs and folk events of the people of Cajabamba, expressed in legends, stories, myths; Morals expressed in the celebration of religious festivals, animal husbandry and agricultural practices, etc., in addition to gastronomy, typical, everyday of the place made from inputs and products of the region and locality. All these folk events mentioned are capable of capturing the active interest and participation of tourists and the community through the practice of Experiential tourism. Each of these folk events received 94% of probation of tourists and / or visitors to experience them as part of experiential tourism in the village of Cajabamba .So it shows the Cajabambina community interested in active participation in the activities includes the practice of experiential tourism with tourists and / or visitors arriving in the village of Cajabamba, which is represented by 99% of respondents expressed their availability. It was used as methods to Inductive method - Deductive, Analytic - Synthetic, ethnographic method, with which it was possible to study and folk events of the people of Cajabamba to practice Experiential tourism.